2004
DOI: 10.1029/2004gl020578
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of ionospheric profile parameters derived from Millstone Hill incoherent scatter radar measurements

Abstract: [1] Diurnal, seasonal, and solar activity variations of the bottomside electron density profile parameters B0 and B1, representing the F2 layer thickness and shape, are studied using a large incoherent scatter radar dataset for Millstone Hill covering the period 1976 -2002. These results are compared with the latest IRI model. Our statistical study is characterized by morning and afternoon falls in the diurnal variation of B0 for seasons other than summer and a $15% change in B1 over a solar cycle, features no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
7
36
1
Order By: Relevance
“…It was found, however, that both model options have their shortcomings as was shown by Lee & Reinisch (2006) (2000) model generally providing better results during daytime, while the Gulyaeva (1987) model performed better during nighttime. This was also confirmed by Lei et al (2004) with Millstone Hill incoherent scatter data. Additionally, like the ionosonde comparisons they found that for B 1 diurnal variations are well represented by the Bilitza et al (2000) model.…”
Section: Electron Densitysupporting
confidence: 66%
“…It was found, however, that both model options have their shortcomings as was shown by Lee & Reinisch (2006) (2000) model generally providing better results during daytime, while the Gulyaeva (1987) model performed better during nighttime. This was also confirmed by Lei et al (2004) with Millstone Hill incoherent scatter data. Additionally, like the ionosonde comparisons they found that for B 1 diurnal variations are well represented by the Bilitza et al (2000) model.…”
Section: Electron Densitysupporting
confidence: 66%
“…The high and low values are depicted by the solid and dashed contours, respectively. Diurnal behavior of B 0 during winter and equinox (from September to March) is characterized by so called morning and evening collapses (Lei et al, 2004) 02 LT) seasonal variations also show an annual pattern with the May minimum (63 km) and the November maximum (75 km). In general, diurnal-seasonal pattern of B 0 is close to that at Millstone Hill (Lei et al, 2004).…”
Section: B 0 Morphologymentioning
confidence: 99%
“…Millstone Hill data (Lei et al, 2004) suggest that increase of solar activity level from low (F 10.7 = 90 s.f.u.) to high (F 10.7 = 180 s.f.u.)…”
Section: B 0 Morphologymentioning
confidence: 99%
See 2 more Smart Citations